Comparison of Alcohol Consumption and Alcohol Policies in the Czech Republic and Norway - Hnilicová, Helena; Nome, Siri; Dobiášová, Karolína; Zvolský, Miroslav; Henriksen, Roger; Tulupova, Elena; Kmecová, Zuzana (Central European journal of public health, 2017)
OBJECTIVE: The Czech Republic is characterized by high alcohol consumption and is well known as the world's biggest consumer of beer. In contrast, the alcohol consumption in Norway is relatively low. In this article, we describe and discuss alcohol policy development in the Czech Republic since the mid-1980s to the present and its impact on the alcohol consumption and compare our findings, including the dynamics of the total alcohol consumption and the development of drinking patterns among young people, with the situation in Norway. METHODS: The study uses the methodology of "process tracing". Selected national statistics, research outcomes and related policy documents were analyzed to identify possible relations between the alcohol consumption and the alcohol policy in two different environments and institutional/policy settings. RESULTS: There was a clear difference in alcohol consumption trends in both countries in the last three decades. Norway was characterized by low alcohol consumption with tendency to decline in the last years. In contrast, the Czech Republic showed an upward trend. In addition, alcohol consumption among Czech youth has been continuously increasing since 1995, whereas the opposite trend has occurred in Norway since the late 1990s. The results revealed that the alcohol-control policies of the Czech Republic and Norway were significantly different during the study period. Norway had a very restrictive alcohol policy, in contrast to the liberal alcohol policy adopted in the Czech Republic, in particular after political transition in 1990. Liberalization of social life together with considerable decline of alcohol price due to complete privatization of alcohol production and sale contributed to an increase of the alcohol consumption in the Czech Republic. CONCLUSIONS: Persistently high alcohol consumption among general population and its growth among young people in the Czech Republic pose social, economic and health threats. Norway could provide the inspiration to Czech politicians about effective options in combating these threats.
Keywords: youth; drinking patterns; Humans; lidé středního věku; Alcohol Drinking; pití alkoholu; Female; Aged; dospělí; senioři; lidé; Norway; Adult; alcohol; ženské pohlaví; alcohol policy; Male; Middle Aged; Public Policy; alcohol consumption; Adolescent; Czech Republic; veřejná politika; Česká republika; mužské pohlaví; Norsko; mladiství